Influence of gyroscopic forces on the stability of a rotating resilient plastic disk under tension - Lila, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
A way of calculation of the Coriolis force is proposed within the small parameter method at the examination of the possible loss of stability of a rotating circular disk, whose axis is rotating with the given angular speed. Proceeding from the Saint-Venant condition of fluidity, a characteristic equation is obtained in the first approximation in respect to the critical radius of the plastic zone. The values of critical angular rotation speed of a disk are numerically determined under for various parameters of the system.